Construction of eukaryotic expression vector of human forkhead box class O6 and its effect on glioma cell survival - GONG Xiaoxia; LI Chao; CAO Xiyue; YANG Chengcheng; HUANG Chao (浙江大学学报. 农业与生命科学版)
To construct the eukaryotic expression vector of human forkhead box class O6 (FOXO6) and explore the effect of FOXO6 on glioma cell survival, we took the cDNA from glioma cell line U251 as a template, and the fragment of FOXO6 gene was amplified by polymerase chain reaction (PCR) and ligated with pRK5-myc vector to construct pRK5-myc-FOXO6 recombinant plasmid. Then, the pRK5-myc-FOXO6 recombinant plasmid and vacant vectors were transfected into U251 cells. The cell viability and the expression of transcription factor peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α) were evaluated by 4’,6-diamidino-2-phenylindole (DAPI) staining and quantitative real-time PCR (qPCR), respectively. The result showed that the recombinant plasmid pRK5-myc-FOXO6 was successfully constructed by double enzyme digestion and DNA sequencing. The transcriptional level of PGC-1α in U251 cells showed a significant decrease after the FOXO6 transfection, and obvious apoptosis occurred after the FOXO6 overexpression. In conclusion, the eukaryotic expression vector of FOXO6 is constructed successfully. In vitro experiments suggest that FOXO6 may inhibit the energy metabolism and anti-oxidation process of U251 cells by inhibiting the expression of PGC-1α, and then induce the apoptosis of U251 cells. These results provide evidences for further in-depth studies exploring the mechanism and target of FOXO6 on glioma.